Between the witness and the observer: what ethnography can learn from James Baldwin - Ince, Jelani I. (Frontiers in Sociology, 2023)
What is the role of the ethnographer during a time of increased racial hostility, political mobilization to keep racial minorities "in their place", and commitments to revisionist interpretations of the country's past and projected future? While the traditional, classic ethnographic approach would recommend that the researcher should avoid taking a stance on socalled political matters and merely observe them, I argue that that position is insufficient to address the issues that people are currently facing. Ethnography can, and should, do more. Therefore, this essay argues that the role of the ethnographer should be oriented towards what the late author James Baldwin calls the witness. The witness is different from the observer because it rejects a positivistic orientation towards ethnographic fieldwork that prioritizes spectatorship to remain "scientific". To be a witness is to transgress traditional epistemological understandings of ethnography that ignores how the researcher's position within the racial system shapes how one knows and does not know, what one sees and does not see, and how one imagines freedom and justice. Ethnographers can learn from Baldwin's method because it provides a rich vocabulary to describe the inequality that research participants encounter while in the field and embraces the possibility of an apocalyptic future, which is a future that is not guaranteed if we continue to seek neutrality. In this article, I detail three lessons that we can learn from Baldwin's method and status position as the witness: (1) Connecting empire to the global racial order via the international outsider; (2) Paying one's dues as a within-nation outsider; and (3) Representing the wretched as a within-community outsider. These lessons are instructive for ethnographers because they provide a lens to understand classic ethnographies of the past, while not wallowing in the doldrums of present arrangements, and challenges future research to ground reality as it is rather than what it "should" be.